Where do we go from here? Prevalence of trachoma three years after stopping mass distribution of antibiotics in the regions of Kayes and Koulikoro, Mali. - Sanoussi Bamani; Jonathan D King; Mamadou Dembele; Famolo Coulibaly; Dieudonne Sankara; Yaya Kamissoko; Jim Ting; Lisa A Rotondo; Paul M Emerson (Public Library of Science (PLoS), 2010)
OBJECTIVES: A national survey in 1997 demonstrated that trachoma was endemic in Mali. Interventions to control trachoma including mass drug administration (MDA) with azithromycin were launched in the regions of Kayes and Koulikoro in 2003. MDA was discontinued after three annual rounds in 2006, and an impact survey conducted. We resurveyed all districts in Kayes and Koulikoro in 2009 to reassess trachoma prevalence and determine intervention objectives for the future. In this paper we present findings from both the 2006 and 2009 surveys. METHODS: Population-based cluster surveys were conducted in each of the nine districts in Koulikoro in 2006 and 2009, whilst in Kayes, four of seven districts in 2006 and all seven districts in 2009 were surveyed. Household members present were examined for clinical signs of trachoma. RESULTS: Overall, 29,179 persons from 2,528 compounds, in 260 clusters were examined in 2006 and 32,918 from 7,533 households in 320 clusters in 2009. The prevalence of TF in children aged 1-9 years in Kayes and Koulikoro was 3.9% (95%CI 2.9-5.0%, range by district 1.2-5.4%) and 2.7% (95%CI 2.3-3.1%, range by district 0.1-5.0%) respectively in 2006. In 2009 TF prevalence was 7.26% (95%CI 6.2-8.2%, range by district 2.5-15.4%) in Kayes and 8.19% (95%CI 7.3-9.1%, range by district 1.7-17.2%) in Koulikoro among children of the same age group. TT in adults 15 years of age and older was 2.37% (95%CI 1.66-3.07%, range by district 0.30-3.54%) in 2006 and 1.37% (95%CI 1.02-1.72%, range by district 0.37-1.87%) in 2009 in Kayes and 1.75% (95%CI 1.31-2.23%, range by district 1.06-2.49%) in 2006 and 1.08% (95%CI 0.86-1.30%, range by district 0.34-1.78%) in 2009 in Koulikoro. CONCLUSIONS: Using WHO guidelines for decision making, four districts, Bafoulabe in Kayes Region; and Banamba, Kolokani and Koulikoro in Koulikoro Region, still meet criteria for district-wide implementation of the full SAFE strategy as TF in children exceeds 10%. A community-by-community approach to trachoma control may now be required in the other twelve districts. Trichiasis surgery provision remains a need in all districts and should be enhanced in six districts in Kayes and five in Koulikoro where the prevalence exceeded 1.0% in adults. Since 1997 great progress has been observed in the fight against blinding trachoma; however, greater effort is required to meet the elimination target of 2015.